Between Justice and Development: How the Indonesian Courts Are Handling Land Disputes in the Face of Industrial Expansion (Indonesian Court and Justice Review, 2025)
Land disputes in Indonesia have intensified with rapid industrial expansion, infrastructure development, and agribusiness growth, often pitting local communities against state-backed corporate interests. This study analyzes how Indonesian courts adjudicate land conflicts, particularly those involving indigenous communities, smallholders, and rural populations affected by development projects. Employing case analysis, field observation, and interviews with litigants, judges, and legal aid providers, the research assesses the judiciary’s capacity to uphold land rights and environmental justice amid developmental pressures. Findings reveal a systemic bias favoring formal land title holders—typically corporations or state entities—over customary or informal land claims. Procedural barriers, lack of legal recognition for indigenous tenure, and limited judicial expertise on land law further disadvantage vulnerable claimants. While some progressive rulings exist, their impact remains limited due to weak enforcement and institutional fragmentation. This study’s novelty lies in its intersectional analysis of land, law, and development, offering a critical lens on how legal institutions mediate conflicts in resource governance. It argues that unless the judiciary is empowered and reoriented toward distributive justice, courts risk becoming instruments of dispossession rather than protectors of rights. The study contributes to wider debates on sustainable development, legal pluralism, and judicial independence in resource-rich developing countries.